2021
DOI: 10.1177/0961203321989794
|View full text |Cite
|
Sign up to set email alerts
|

Association of PER2 gene single nucleotide polymorphisms with genetic susceptibility to systemic lupus erythematosus

Abstract: The circadian clock plays a crucial role in the progress of systemic lupus erythematosus (SLE). In this study, we performed a case-control study to explore the association between Period 2 (PER2) gene single nucleotide polymorphisms (SNPs) and the susceptibility of systemic lupus erythematosus (SLE). A total of 492 SLE patients and 493 healthy controls were included. The improved multiple ligase detection reaction (iMLDR) was used for genotyping. The correlations between four SNPs of PER2 (rs10929273, rs118944… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
(33 reference statements)
1
4
0
Order By: Relevance
“…24 25 Furthermore, animal models have confirmed the existence of a dependence relationship between the expression of CLOCK and the activity of inducible nitric oxide synthase, 26 which is found to be overproduced in the context of lupus activity. 27 In addition, Dan et al found that PER2 gene SNPs were related to the genetic 28 This result is consistent with our findings. The expression of PER1 was higher in LN and flare-activated SLE, whereas CRY1 and CLOCK were higher in these subpopulations.…”
Section: Discussionsupporting
confidence: 92%
“…24 25 Furthermore, animal models have confirmed the existence of a dependence relationship between the expression of CLOCK and the activity of inducible nitric oxide synthase, 26 which is found to be overproduced in the context of lupus activity. 27 In addition, Dan et al found that PER2 gene SNPs were related to the genetic 28 This result is consistent with our findings. The expression of PER1 was higher in LN and flare-activated SLE, whereas CRY1 and CLOCK were higher in these subpopulations.…”
Section: Discussionsupporting
confidence: 92%
“…Complementing this finding, additional research suggests that relatives of SLE patients who consistently sleep less than 7 h per night face an elevated risk of developing the disease 182 . Moreover, genetic factors contribute to this correlation as evidenced by the association of single nucleotide polymorphisms in the PER2 gene with both the susceptibility to and clinical manifestations of SLE 183 . Conversely, patients with SLE, or those at risk of developing it, often experience sleep disturbances, which significantly impair their quality of life 184 …”
Section: Circadian Regulation Of Diseasesmentioning
confidence: 99%
“…182 Moreover, genetic factors contribute to this correlation as evidenced by the association of single nucleotide polymorphisms in the PER2 gene with both the susceptibility to and clinical manifestations of SLE. 183 Conversely, patients with SLE, or those at risk of developing it, often experience sleep disturbances, which significantly impair their quality of life. 184 Studies have highlighted the role of circadian clock proteins in the pathogenesis of SLE.…”
Section: Systemic Lupus Erythematosus (Sle)mentioning
confidence: 99%
“…3 ), an important enzyme for DNA methylation, has been found to have a positive correlation with disease severity and with co-existing periodontitis in the Brazilian population, depicting the interplay between genetics and epigenetic factors and lupus pathology [ 54 ]. Polymorphism associated with circadian rhythms can also play an important role in disease, where the SNP in the Period 2 gene (PER2), a circadian clock regulatory gene, was also found to be positively associated with the clinical manifestation of SLE pathogenesis [ 55 ]. Furthermore, analysis of SNP in various cytokines including IL-1β, IL-17, and IL-10 (Fig.…”
Section: Genetic Factorsmentioning
confidence: 99%